Anti‐glomerular basement membrane disease (Goodpasture disease): From pathogenesis to plasma exchange to IdeS. Issue 1 (10th August 2021) - Shin, Jae Il; Geetha, Duvuru; Szpirt, Wladimir M.; Windpessl, Martin; Kronbichler, Andreas
Abstract: Anti‐glomerular basement membrane (GBM) disease (Goodpasture disease) often presents with severe kidney failure and pulmonary hemorrhage. Anti‐GBM antibodies are pathogenic, and other autoantibodies such as laminin‐521 have been identified recently, potentially indicating a subset with a more severe disease phenotype and poor prognosis. Around 30%–40% of patients are also anti‐neutrophil cytoplasmatic antibody (ANCA)‐positive and this subset combines features of anti‐GBM disease and ANCA‐associated vasculitis, with particular impact on long‐term treatment. A combination of therapeutic plasma exchange (or immunoadsorption), cyclophosphamide, and glucocorticoids is considered standard of care management, but despite early initiation, patients with poor prognostic factors often remain dialysis dependent. Imlifidase (IdeS), capable to cleave IgG within hours, has been tested in a phase II trial. Among 15 patients, 10 with poor prognosis at baseline (eGFR <15 ml/min/1.73 m 2 ) were dialysis independent at 6 months. Further developments are needed to refine treatment approaches in anti‐GBM disease.